From BSA to CPA: Accounting the Journey Towards Becoming Certified Public Accountants in the City of Koronadal - Tadlas, Ned Angelo A.; Java, Sarah May S.; Palacio, Princess Erlynn P.; Rejas, Nicole M.; Relampago, Diona Kaye Maria M.; Sarmiento, Hessa S.; Gonzales, James Edward T.; Gaygay Jr. , Carlos Friales (Future Science / FSH-PH Publications, 2025)
This study aimed to describe the experiences and perceptions of Certified Public Accountants (CPAs) regarding their Bachelor of Science in Accountancy (BSA) course, their careers as CPAs, and their sources of motivation. A total of five (5) CPAs residing in the City of Koronadal were interviewed using a Descriptive Qualitative Design. The participants were selected through purposive sampling based on inclusion criteria. Data collection involved researcher-made, open-ended interview guide questionnaires, and interviews were conducted online via Google Forms. Thematic analysis, following Braun and Clarke’s (2006) approach, was used to analyze their responses. The results revealed that participants during their time as accountancy students perceived the said profession as prestigious and financially rewarding. However, they faced significant challenges, including the mental demands of coursework, social isolation due to academic pressures, and financial constraints that affect their studies. When they became CPAs, their motivations shifted as they now balance extrinsic factors such as financial stability and family support with intrinsic motivations like personal growth and career fulfillment. Despite this, they continue to encounter stress, time management difficulties, and the pressure of continuous learning to stay competitive in the field. This study unfolded that while the accounting profession is challenging, motivation helps students and CPAs overcome obstacles and find success. Aspiring CPAs should develop strong financial expertise and perseverance. Likewise, CPAs must pursue continuous learning and mentorship, educators and policymakers should enhance practical training and support systems, and future researchers are encouraged to expand their sample sizes for deeper analysis.